Squamous Cellular Carcinoma Antigen Serum Determination as a Biomarker of Barrett Esophagus and Esophageal Cancer: A Phase III Study. Issue 5 (May 2018) - Maddalo, Gemma; Fassan, Matteo; Cardin, Romilda; Piciocchi, Marika; Marafatto, Filippo; Rugge, Massimo; Zaninotto, Giovanni; Pozzan, Caterina; Castoro, Carlo; Ruol, Alberto; Biasiolo, Alessandra; Farinati, Fabio
Abstract : Goal: To evaluate the potential role of the determination of the immunocomplexed form of squamous cell carcinoma antigen [SCCA-immunoglobulin (Ig)M] for the screening of Barrett esophagus (BE) and esophageal adenocarcinoma (EAC). Background: The cost-effectiveness of surveillance in BE is still debated and the use of biomarkers in screening and surveillance still not recommended. No information is available regarding SCCA-IgM determination in BE. Study: SCCA-IgM levels were determined (enzyme-linked immunosorbent assay) in 231 patients prospectively recruited, 71 with BE, 53 with EAC, and 107 controls, including 42 blood donors and 65 patients with gastroesophageal reflux. SCCA-IgM cutoffs between BE/EAC and controls and for BE "at risk" versus short nondysplastic BE were calculated by receiver operating characteristic curves. Immunostaining for SCCA-IgM was obtained in a subgroup of patients. Results: Median SCCA-IgM values were significantly higher in BE and EAC than in controls ( P =0.0001). Patients with SCCA-IgM levels above the cutoff had a 33 times higher relative risk of harboring BE or EAC ( P =0.0001). Patients "at risk, " with long or dysplastic BE had SCCA-IgM levels significantly higher than those with short nondysplastic BE ( P =0.035) and patients with SCCA-IgM above the cutoff had a 8 times higher relative risk of having BE "at risk." SCCA was expressed in Barrett mucosa but not in cardiac metaplasia. Conclusions: Serum SCCA-IgM determination allows the identification of patients at risk for BE/EAC and the stratification of BE patients in subgroups with different cancer risk. Because of the still limited number of controls, large, prospective studies are required to confirm this evidence.